Central and peripheral muscle fatigue following repeated-sprint running in moderate and severe hypoxia - Townsend, N.; Brocherie, F.; Millet, G. P.; Girard, O. (Experimental Physiology, 2020)
We examined the effects of increasing hypoxia severity on repeated-sprint running performance and neuromuscular fatigue. Thirteen active males completed eight 5-s sprints (recovery = 25 s) on a motorized sprint treadmill in normoxia (SL; FiO2 0.21), in moderate hypoxia (MH; FiO2 0.17), and severe hypoxia (SH; FiO2 0.13). Following 6 min of passive recovery, in all conditions a second set of four sprints of 5 s was conducted in normoxia. Neuromuscular function of knee extensors was assessed at baseline (Pre-), and 1 min after set 1 (Post-set 1) and set 2 (Post-set 2). In set 1, mean distance covered in SL (22.9 ± 1.2 m) was not different to MH (22.7 ± 1.3 m; P = 0.71), but was greater than in SH (22.3 ± 1.3 m; P = 0.04). No significant differences between conditions for mean distance occurred in set 2. There was a decrease in maximal voluntary contraction (MVC) torque (Delta = -31.4 ± 18.0 Nm, P < 0.001) and voluntary activation (%VA; Delta = -7.1 ± 5.1%, P = 0.001), from Pre- to Post-set 1, however there was no effect of hypoxia. No further change from Post-set 1 to Post-set 2 occurred for either MVC or %VA. The decrease in potentiated twitch torque in SL (? = -13.3 ± 5.2 Nm), was not different to MH (Delta = -13.3 ± 6.3 Nm), but was lower than in SH (Delta = -16.1 ± 4 Nm) from Pre- to Post-set 1 (interaction: P < 0.003). Increasing severity of normobaric hypoxia, up to an equivalent altitude of 3600 m, can increase indices of peripheral fatigue, but does not impact central fatigue following "all-out" repeated-sprint running.